Exploring the Utility of Theory-Informed Methodological Approaches in Youth Harassment Research - Garnett, Bernice Raveche (Journal of interpersonal violence, 2021)
In comparison to research on youth bullying, less research has been dedicated to youth harassment experiences in school. This study seeks to illustrate youth harassment experiences in school through three theoretically informed methodological approaches to modeling youth victimization: binary, cumulative risk, and attributional approaches. Data come from the 2015 Vermont School Climate Pilot Survey (N = 2,589 students). Students with complete harassment information (N = 2,481) were included. Using theoretically informed methodological approaches, regression models examined the associations between experiencing harassment (binary, attributions, and cumulative) and school connection, safety, and equity. About 16% of the sample experienced some form of harassment during the current school year (2014-2015). The most prominent attributions of harassment include weight (40%), sex (27%), and race (22%). After controlling for sociodemographics, ever experiencing harassment was associated with lower school safety, –0.73 (β), p < .001, lower connection with school, –0.52 (β), p < .001, and lower perceived equity, –0.77 (β), p < .001. Experiencing harassment is negatively related to school climate. The results from these analyses underscore the negative relationship among harassment victimization and several important indicators of school climate including student connection, perceived safety at and to/from school, and perceived equity of school. Theoretically informed methodological approaches in youth harassment research should be advanced to comprehensively assess the relationship between harassment victimization and harassment attributes on the social, academic, and behavioral development of youth.